2006
DOI: 10.1111/j.0014-3820.2006.tb01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of the Cryptic Species Complex of Acanthocyclops Vernalis (Crustacea: Copepoda). Ii. Crossbreeding Experiments, Cytogenetics, and a Model of Chromosomal Evoloution

Abstract: Abstract. Collectively, populations of Acanthocyclops vernalis, a species complex of freshwater copepods, are remarkably similar as to morphology and DNA content, despite variability in chromosome number. Reproductive isolation had been reported among some populations, but with each new investigation the species boundaries and factors that may influence them appeared less clear. To clarify the pattern of biological species within this group of populations, we adopted a comprehensive approach and examined patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the present study, we successfully produced F1 and F2 hybrid L. salmonis strains using maternal lines from both the Pacific and the Atlantic. Previous studies of separate conspecific populations of copepods have shown that although defined as single species, the populations may or may not be reproductively compatible [36-38]. In studies of the intertidal copepod Tigriopus californicus it has been shown that “Dobzhansky-Muller incompatibilities” between strains, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we successfully produced F1 and F2 hybrid L. salmonis strains using maternal lines from both the Pacific and the Atlantic. Previous studies of separate conspecific populations of copepods have shown that although defined as single species, the populations may or may not be reproductively compatible [36-38]. In studies of the intertidal copepod Tigriopus californicus it has been shown that “Dobzhansky-Muller incompatibilities” between strains, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…They also form the largest biomass of all animals in the world’s oceans, and possibly on the planet ( Hardy 1956 ; Huys and Boxshall 1991 ; Humes 1994 ; Verity and Smetacek 1996 ). Copepods are particularly known to frequently exhibit cases of cryptic speciation, where large genetic distances and reproductive isolation are accompanied by morphological stasis ( Burton 1990 ; Ganz and Burton 1995 ; Edmands 1999 ; Lee 2000 ; Lee and Frost 2002 ; Goetze 2003 ; Grishanin et al 2006 ; Rynearson et al 2006 ; Eyun et al 2007 ; Chen and Hare 2011 ). In the absence of morphological cues and differentiation, it has been hypothesized that speciation in copepods occurs through rapid evolution of chemical sensing ( Snell and Morris 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…These chromosomal fusions likely played a crucial role in speciation processes within this species complex 48,57 . Chromosomal fusions are increasingly recognized as important drivers of speciation, especially in systems where closely related species or populations exhibit divergent karyotypes 4,16,47,[70][71][72] . Chromosomal changes can promote speciation events by impeding gene ow between populations, thereby facilitating the accumulation of genetic differences among them 4,16,47,70,72 .…”
Section: Impacts Of Genome Architecture On Selection Responsementioning
confidence: 99%